The Emotional Effectiveness of Advertisement - Otamendi, F. J.; Sutil Martín, Dolores Lucia (Frontiers in Psychology, 2020)
Based on cognitive-emotional neuroscience, the effectiveness of advertisements is measured in terms of individuals’ unconscious emotional responses. Using AFFDEX to record and analyze facial expressions, a combination of indicators that track both basic emotions and individual involvement is used to quantitatively determine if a spot causes high levels of ad liking in terms of attention, engagement, valence and joy. We use as a test case a real campaign, in which a spot composed of 31 scenes (images, text and the brand logo) is shown to subjects divided into 5 groups in terms of age and gender. The target group of mature women shows statistically more positive emotions and involvement than the rest of groups, demonstrating the emotional effectiveness of the spot. Each other experimental groups show specific negative emotions as a function of their age.